Reconcilling stability and growth: smart pacts and structural reforms - Beetsma, Roel M.W.J.; Debrun, Xavier (2004)
This paper analyzes the decision by a government facing electoral uncertainty to implement structural reforms in the presence of fiscal restraints similar to the Stability and Growth Pact. To the extent that the reform package entails budgetary costs, the model shows that a fiscal pact erodes incentives to carry out structural reforms, sacrificing future growth for present stability. Although the pact effectively addresses the deficit bias resulting from electoral uncertainty, the induced reduction in reforms implies ambiguous welfare effects. We conclude that a "smart" (i.e., welfare-improving) pact should take into account the budgetary effects of structural reforms. Our conclusions are consistent with the actual principles guiding the implementation of the Stability and Growth Pact. - Reproduced.
Keywords: Structural adjustment; Economic growth; Economic reform